Deteksi Kemiripan Abstraksi Tugas Akhir Diploma Informatika Universitas AMIKOM Yogyakarta dengan Algoritma Rabin Karp - Siti Fatonah; Arifiyanto Hadinegoro; Anggit Dwi Hartanto (STMIK Budi Darma, 2020)
The practice of plagiarism in writing is quite common, both public and academic. Plagiarism is an act of abuse, theft, deprivation, publishing, statement, or declaring itself as a thought, idea, writing, or creation that actually belongs to someone else. For manual checking, whether a work is categorized as a work of plagiarism or a book is definitely a long time. Therefore, an application is needed that can detect the level of originality of a work more effectively, efficiently, and accountably. The application process is to find the basic words in the final assignment abstraction with the steaming method being tested. After obtaining the basic words of each word, formed gram and searched for hash values using the Rabin Karp algorithm. The final assignment abstraction hash value will be tested compared to the Final Task abstraction value in the database. It is expected to find out how much the level of plagiarism abstraction with the final task testing mechanism looking for presentation of final assignment similarity abstraction value compared to the final assignment abortion of the database and the comparison results in percent form, stored in the database and displayed in the system sequentially from the total presentation similarity of the biggest to the smallest.